2020
DOI: 10.3390/biology9020022
|View full text |Cite
|
Sign up to set email alerts
|

Centrifugation Force and Time Alter CASA Parameters and Oxidative Status of Cryopreserved Stallion Sperm

Abstract: Conventional sperm selection techniques used in ARTs rely on centrifugation steps. To date, the different studies reported on the effects of centrifugation on stallion sperm motility provided contrasting results and do not include effects on mitochondrial functionality and different oxidative parameters. The effects of different centrifugation protocols (300× g for 5′, 300× g for 10′, 1500× g for 5′ and 1500× g for 10′ vs. no centrifugation) on motility and oxidative status in cryopreserved stallion sperm, wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 59 publications
(82 reference statements)
2
8
0
Order By: Relevance
“…However; the mechanical actions of centrifugation and spermatozoa compaction at the bottom could reduce sperm quality [ 48 ]. We observed that TM and velocities of spermatozoa declined after sperm washing, in agreement with Marzano et al [ 49 ] in equine sperm. In a previous study, we observed a beneficial effect of sperm washing on motility in goats [ 18 ] without a significant deleterious effect of the centrifugation process, in agreement with others [ 47 ].…”
Section: Discussionsupporting
confidence: 93%
“…However; the mechanical actions of centrifugation and spermatozoa compaction at the bottom could reduce sperm quality [ 48 ]. We observed that TM and velocities of spermatozoa declined after sperm washing, in agreement with Marzano et al [ 49 ] in equine sperm. In a previous study, we observed a beneficial effect of sperm washing on motility in goats [ 18 ] without a significant deleterious effect of the centrifugation process, in agreement with others [ 47 ].…”
Section: Discussionsupporting
confidence: 93%
“…However, there seems to be a general absence of research on the impact of centrifugation on any mammalian cells. In fact, most of the scant existing literature stems from the medical fields andrology and urology [ 33 , 34 , 35 ]. Interestingly, results of those studies on sperm cells are quite similar to our data on neutrophils: Marzano et al were able to show, that with increasing g -force and duration of centrifugation, sperm cells suffered a major loss in motility compared to non-centrifuged samples [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, most of the scant existing literature stems from the medical fields andrology and urology [ 33 , 34 , 35 ]. Interestingly, results of those studies on sperm cells are quite similar to our data on neutrophils: Marzano et al were able to show, that with increasing g -force and duration of centrifugation, sperm cells suffered a major loss in motility compared to non-centrifuged samples [ 34 ]. Furthermore, Zini et al, as well as Marzano et al, observed a significant decrease in DNA integrity in centrifuged sperm cells in comparison to controls [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…We tested a 200× g force, not previously described for cryopreserved stallion sperm and its effect on motility. As previously reported, we found that total sperm motility was negatively affected by centrifugation times longer than 2 min, even at lower g-forces [65]. In this work, we have used samples that were frozen poorly (<35% motility post-thawing) [67], suggesting that a better outcome could be possible using samples with better post-thaw motility.…”
Section: Discussionmentioning
confidence: 75%
“…Moreover, several sperm selection protocols used during ARTs require multiple centrifugations. It was previously described that different conditions of centrifugation alter motility and oxidative status, and consequently increase the DNA damage of cryopreserved stallion sperm [ 65 , 66 ]. We tested a 200× g force, not previously described for cryopreserved stallion sperm and its effect on motility.…”
Section: Discussionmentioning
confidence: 99%